Preclinical progress and first translational steps for a liposomal chemotherapy protocol against adrenocortical carcinoma. Issue 10 (October 2016) - Jung, Sara; Nagy, Zoltan; Fassnacht, Martin; Zambetti, Gerard; Weiss, Max; Reincke, Martin; Igaz, Peter; Beuschlein, Felix; Hantel, Constanze
Abstract : Systemic therapy of adrenocortical carcinoma (ACC) is limited by heterogeneous tumor response and adverse effects. Recently, we demonstrated anti-tumor activity of LEDP-M (etoposide, liposomal doxorubicin, liposomal cisplatin, mitotane), a liposomal variant of EDP-M (etoposide, doxorubicin, cisplatin, mitotane). To improve the therapeutic efficacy and off-target profiles of the clinical gold standard EDP-M, we investigated liposomal EDP-M regimens in different preclinical settings and in a small number of ACC patients with very advanced disease. Short- and long-term experiments were performed on two ACC models (SW-13 and SJ-ACC3) in vivo . We evaluated the anti-tumoral effects and off-target profiles of EDP-M, LEDP-M and a novel regimen L(l)EDP-M including liposomal etoposide. Furthermore, the role of plasma microRNA-210 as a therapeutic biomarker and first clinical data were assessed. Classical and liposomal protocols revealed anti-proliferative efficacy against SW-13 (EDP-M P  < 0.01; LEDP-M: P  < 0.001; L(l)EDP-M: P  < 0.001 vs controls), whereas in SJ-ACC3, only EDP-M ( P  < 0.05 vs controls) was slightly effective. Long-term experiments in SW-13 demonstrated anti-tumor efficacy for all treatment schemes (EDP-M: P  < 0.01, LEDP-M: P  < 0.05, L(l)EDP-M P  < 0.001 vs controls). The analysis of pre-defined criteria leading to study termination revealed significant differences for control ( P  < 0.0001) and EDP-M ( P  = 0.003) compared to L(l)EDP-M treatment. Raising its potential for therapy monitoring, we detected elevated levels of circulating microRNA-210 in SW-13 after LEDP-M treatment ( P  < 0.05). In contrast, no comparable effects were detectable for SJ-ACC3. However, overall histological evaluation demonstrated improved off-target profiles following liposomal regimens. The first clinical data indicate improved tolerability of liposomal EDP-M, thus confirming our results. In summary, liposomal EDP-M regimens represent promising treatment options to improve clinical treatment of ACC.